Sámi new speakers: A case study of the North Sámi language beginner program at UiT - Ghiorghilas, Oana Maria (UiT Norges arktiske universitet, 2021)
The present thesis focuses on students enrolled at UiT The Arctic University of Norway (UiT) during the 2020/2021 academic year in the Nordsamisk som fremmedspråk, North Sámi beginner language program. The study explores the process of becoming a Sámi new speaker through an educational program and the factors that motivate, promote, or prevent new speakers’ learning path. New speakers can contribute to maintaining, and hopefully, increasing the number of Sami speakers. What are students’ experiences and challenges in using Sámi language outside the Sámi administrative areas, in an urban environment such as Tromsø? And what is the role of the language program in this process? The beginner North Sámi language program at UiT accommodates students who have a direct link to Sámi language and culture, and students who have not. Yet, both groups represent agency in learning and supporting the Sámi language. Students are not categorized as successful or unsuccessful in this study, as learning a language is a multifaceted experience influenced by individual, community, and societal factors. The research discusses how all factors have an impact on the use of Sámi language outside the classroom. A personal interest in learning the language as well as a professional aim, represent high motivational factors for learners to enroll in the program. What are the opportunities then for students to use Sámi after the one-year language program? The empirical case study of the North Sámi language learners at UiT offers a ground of analysis and discussion on the topics of education, language revitalization and Sámi language status within the Norwegian society. It discusses challenges, demanding learning processes, but overall, it addresses the possibility of becoming a Sámi new speaker through education.